Global human resource management managing people in developing and transitional countries - McCourt, Willy; Eldridge, Derek, 1942-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar Pub., 2003)
This book presents Human Resource Management (HRM) as a tool for improving the performance of organizations in developing and transitional countries. It does this through the presentation of an integrated model of human resource management, informed by the practical realities of applying such a model in developing and transitional countries.
1. Global human resource management : a 'crossvergent' approach. -- 2. Strategic human resource management -- 3. Human resource planning -- 4. Job analysis -- 5. Managing pay -- 6. Recruitment, selection and equal opportunities -- 7. Performance management and appraisal -- 8. Learning and training -- 9. Job reduction -- 10. Employee relations.
Includes bibliographical references (p. 365-370) and indexes.
Keywords: Personnel management -- Developing countries; International business enterprises -- Developing countries -- Personnel management; Electronic books